The Differences in Influence of Approaches and Learning Styles on Learning Outcomes in the Matter Material of Class IV Students at SD IT Tadzkia, Langsa - Kamal Fahlevi; KMS Amin Fauzi; Sumarno Sumarno (BIRCU, 2020)
In mathematics learning, the determination of the approach greatly determines student learning outcomes, because mathematics subjects are assessed for students as quite difficult subjects, this assessment appears due to the discomfort experienced by students during the learning process in class. The method used in this research is an experimental method with two-way ANOVA test analysis. This study aims to determine differences in learning outcomes through the PMR and PMR approaches based on the Math App game in terms of student learning styles. The research was conducted at SD IT Tadzkia Langsa with a total sample of 34 students. The data collection technique uses the distribution of learning style questionnaires and by conducting tests (pre-test and post-test). This study found that there were differences in learning income between PMR and PMR based on the Math App game based on a significant value of 0.045 <0.05. Then there were also differences in learning styles based on the results of the SPSS calculation with a significant value of 0.049 <0.05. Whereas in the interaction section between the learning style approach and learning style, it was found that there was an interaction between the learning style approach and the learning style with a significant value of 0.018 <0.05.